Phenotypic Analysis of Qualitative Traits in Local Ducks of Kediri Regency, East Java - Nurwahyuni, Eka; Septama, Azivina Happy; Agustin, Rahma Ayu Dwi; Wati, Anif Mukaromah (CV. Komunitas Dunia Peternakan, 2026)
This study aimed to identify the qualitative characteristics of local ducks in Kediri Regency, East Java, as a foundational basis for breeding and genetic improvement programs. A total of 250 female local ducks were observed across five subdistricts using purposive sampling. Data were collected through direct observation of feather color patterns and beak color and were analyzed descriptively. The results showed that all observed ducks had black beaks (100%) and brown head feathers (100%). Additional dominant characteristics included white feathers above the eyes (96%), brown wing feathers (98%), brown back feathers (100%), brown tail feathers (98%), and brown thigh feathers (100%). These findings indicate that Kediri local ducks are predominantly characterized by brown plumage with distinctive white stripes above the eyes and solid black beaks. The observed variations in feather and beak color are influenced by genetic factors, particularly melanin and lipochrome pigments. This study provides essential baseline data to support selective breeding strategies, genetic conservation, and the sustainable development of local duck resources, thereby contributing to regional livestock improvement programs.